2011
DOI: 10.1016/j.bbmt.2010.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Seroprotective Titers against 2009 H1N1 Influenza A Virus after Vaccination in Allogeneic Hematopoietic Stem Cell Transplantation Recipients

Abstract: Little data are available regarding the safety and immunologic response to pandemic H1N1 influenza vaccine in recipients of allogeneic hematopoietic stem cell transplantation (HSCT). We measured serum antibody titers against A/California/7/2009 H1N1 using a hemagglutination inhibition assay in 82 allogeneic HSCT recipients who received the 2009 H1N1 vaccine between November 2009 and January 2010 after it became available at our institution. The median time between HSCT and vaccination was 19 months (range, 2.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
59
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 18 publications
10
59
3
Order By: Relevance
“…We found a seroconversion and seroprotection rate of 42% (15/36), which is similar to rates reported on pandemic H1N1 (2009) vaccination in alloHSCT and autoHSCT patients by Issa et al [13] and Engelhard et al [15]. Previous studies of pandemic H1N1 (2009) vaccination in healthy people showed seroconversion in >90% within 21 days of vaccination [20,21].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…We found a seroconversion and seroprotection rate of 42% (15/36), which is similar to rates reported on pandemic H1N1 (2009) vaccination in alloHSCT and autoHSCT patients by Issa et al [13] and Engelhard et al [15]. Previous studies of pandemic H1N1 (2009) vaccination in healthy people showed seroconversion in >90% within 21 days of vaccination [20,21].…”
Section: Discussionsupporting
confidence: 90%
“…Although Issa et al were not able to show a statistically significant influence of the presence of GvHD and concurrent immunosuppressive therapy (including prednisone) on the rate of seroprotection against pandemic H1N1 (2009) influenza virus, the trends were similar to our results: 59% of patients without GvHD had seroprotective titers, while 44% of those with aGvHD or cGvHD had seroprotective titers [13].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations